Long noncoding RNA MALAT1 suppresses breast cancer metastasis. (December 2018) - Kim, Jongchan; Piao, Hai-Long; Kim, Beom-Jun; Yao, Fan; Han, Zhenbo; Wang, Yumeng; Xiao, Zhenna; Siverly, Ashley; Lawhon, Sarah; Ton, Baochau; Lee, Hyemin; Zhou, Zhicheng; et al.
Abstract MALAT1 has previously been described as a metastasis-promoting long noncoding RNA (lncRNA). We show here, however, that targeted inactivation of theMalat1 gene in a transgenic mouse model of breast cancer, without altering the expression of its adjacent genes, promotes lung metastasis, and that this phenotype can be reversed by genetic add-back ofMalat1 . Similarly, knockout of MALAT1 in human breast cancer cells induces their metastatic ability, which is reversed by re-expression of Malat1. Conversely, overexpression of Malat1 suppresses breast cancer metastasis in transgenic, xenograft, and syngeneic models. Mechanistically, the MALAT1 lncRNA binds and inactivates the prometastatic transcription factor TEAD, preventing TEAD from associating with its co-activator YAP and target gene promoters. Moreover, MALAT1 levels inversely correlate with breast cancer progression and metastatic ability. These findings demonstrate that MALAT1 is a metastasis-suppressing lncRNA rather than a metastasis promoter in breast cancer, calling for rectification of the model for this highly abundant and conserved lncRNA. Targeted inactivation, restoration and overexpression of MALAT1 in multiple in vivo models demonstrate that the lncRNA MALAT1 suppresses breast cancer metastasis through binding and inactivation of the pro-metastatic transcription factor TEAD.